Assessment of OSINT results in judicial practice: selected issues - Hloviuk, I.V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article examines the assessment of OSINT results in judicial practice through the criteria of relevance, admissibility, and reliability. Attention is drawn to instances where the relevance, admissibility, and reliability of such evidence have been challenged. The approaches of the Criminal Cassation Court to this issue are presented. The effectiveness of such challenges is analysed in detail on the example of the decision of the Criminal Cassation Court in case no. 201/11849/23, in the context of the defence’s arguments and the counter-arguments (regarding the relevance, admissibility, and reliability of factual data). It is concluded that, where OSINT results are recorded in a report under Article 237 of the Code of Criminal Procedure of Ukraine with annexes, the report itself constitutes the source of evidence, as a type of document. Accordingly, issues of admissibility may concern exclusively the manner in which the inspection was conducted and recorded, compliance with the requirements of the Code of Criminal Procedure of Ukraine as to the competent authority, the time limits of the pre-trial investigation, and other procedural aspects of the collection and recording of the data contained in the report. By contrast, if doubts arise concerning the content of the originally recorded data, their origin in open sources (the author of the content, the person who published it, and the purpose of such publication), their possible creation by artificial intelligence, their creation and dissemination for the purpose of disinformation, the correctness of their technical collection, the immutability of online content of any kind, metadata, or hash values, the issue at stake is the reliability of the evidence. In this situation, initiating a claim for the recognition of such factual data as inadmissible evidence is meaningless. OSINT results may contain factual data that lack the quality of relevance, but this is in no way connected with the analysis of their source – namely, open data – since relevance is determined by the existence (or absence) of a connection with the circumstances subject to proof. Accordingly, initiating a claim for the recognition of evidence as irrelevant on the basis of doubts concerning the content of the originally recorded data or their origin in open sources (the author of the content, the person who published it, and the purpose of such publication) is also meaningless. In judicial decisions, OSINT results must be presented in such a way that an impartial observer can understand why the court considers them reliable. The foundation for this lies in proper recording during the pre-trial investigation, in compliance with the recommendations of the Berkeley Protocol.